On the Role of Social Comparisons in Shaping Migrants' Remittance Behavior: Theory, and Evidence from China - Oded Stark; Daniel LaFave (World Scientific Handbook of Global Migration, Volume 2: Global Migration: Alternative Views and Social Comparisons, 2024)
We model how the remittances by a migrant are influenced by the remittance behavior of fellow migrants with whom the migrant compares himself. We show that an increase in the mean remittances of the group of fellow migrants encourages the migrant to increase his own remittances, and that this response holds only for those who lag behind the group mean. We test the model using longitudinal data on rural-to-urban migrants in major Chinese cities. We find support for the model's predictions. Our results have implications for modeling remittance behavior and for the role of social comparisons in economic decisions.
Keywords: D13; F22; F24; O15; O53; 330; Mean remittances of a migrant's reference group; A migrant's own remittances; Social comparisons